Tuber Crops
The book treats a subject that has remained largely on the fringes of academic debate despite it being related to one of most sustainable agricultural products available in India. This book covers fifteen major and minor tuber crops and throws light on their uses, cultivation process, irrigation needs and related issues in a simple and non-technical language.